2018
DOI: 10.14214/df.262
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of dissolved carbon and nitrogen in decomposing boreal mor and peat as affected by enchytraeid worms

Abstract: Export of dissolved organic carbon and nitrogen (DOC and DON) from terrestrial ecosystems to watercourses has increased in the boreal zone. However, the effects of decomposing material and soil food webs on the release rate and quality of DOC and DON are poorly known. The objective of this study was to quantify the release of carbon (C) and nitrogen (N) from mor and peat, which are the most common organic soil types in the boreal zone. The impact of soil fauna on the release processes was also estimated. Decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 99 publications
1
4
0
Order By: Relevance
“…Temperature sensitivity patterns were evaluated for each soil type and soil faunal treatment. This study continues the works presented by Laurén et al [27] and Lappalainen et al [5,28], who demonstrated the role of soil fauna and soil type on different C and N release rates but did not study the effect of abiotic factors, such as temperature and moisture on C and N release.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Temperature sensitivity patterns were evaluated for each soil type and soil faunal treatment. This study continues the works presented by Laurén et al [27] and Lappalainen et al [5,28], who demonstrated the role of soil fauna and soil type on different C and N release rates but did not study the effect of abiotic factors, such as temperature and moisture on C and N release.…”
Section: Introductionsupporting
confidence: 90%
“…The studies by Conant et al [45] and Hamdi et al [46] suggest that C release rate at the beginning of incubation is highest but stabilizes after the labile C has been consumed (approximately after 50 days). Our previous experiments [5,27,28] with the same soil types show that the compound storage in the repeated measurements change linearly between 50 to 180 days of incubation. Linearity allowed us to use a single value, the rate of storage change (γ), as a response variable in the further analyses, thus facilitating a balanced comparison of different treatments and compounds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high soil water enabled rapid transport of water and mobilization of nutrients. Retention of ammonium and nitrate following fertilization might have been influenced by organic nitrogen mineralization and nitrification driven by many microorganism pathways that occur mainly at the upper part of (Jauhiainen et al 2012a;Lappalainen et al 2013;Martínez et al 2018). The control treatments (T5 and T6) did not improve ammonium and nitrate ion retention throughout the pineapple growth period because soil acidity restricts nitrification and mineralization of organic nitrogen to ammonium ions.…”
Section: Ammonium and Nitrate In Tropical Peat Soils Cultivated With mentioning
confidence: 99%
“…Because ammonium ions are attracted to negatively charged soil colloids of peat soils, they do not leach rapidly like potassium. However, ammoniums are relatively unstable in drained peat soils because they are rapidly converted to nitrate (Lappalainen et al 2013).…”
Section: Introductionmentioning
confidence: 99%